The surface structure and the deep structure of sequential control: What can we learn from task span switch costs? - Mayr, Ulrich (Psychonomic bulletin & review, 2010)
A large component of response time switch costs in the cued task-switching paradigm is linked to cue changes without task changes, suggesting costs might reflect passive priming rather than endogenous control. In contrast, the task span procedure requires subjects to guide task selection via sequences of memorized task cues and therefore may be better suited to reflect endogenous switch processes (Logan, 2004). The present experiments combined the task span procedure with a 2:1 mapping between cues and tasks, allowing separation of cue-switch costs from true task-switch costs. Replicating findings with the cued task-switching paradigm, results showed both substantial cue-switch costs and actual task-switch costs (Experiments 1 and 2) as well as sensitivity of cue-switch costs, but not of task-switch costs, to opportunity for preparation (Experiment 2). Apparently, simple action plans use “surface level” phonological or articulatory codes that contain no task information. These results suggest that the distinction between cue-related and task-related processes is critical no matter whether tasks are cued exogenously or endogenously.